1984
DOI: 10.1093/oxfordjournals.jbchem.a135015
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Local Positive Charges on Cytochrome f for Electron Transfer to Plastocyanin and Potassium Ferricyanide1

Abstract: To study the relationship between the electron transfer rate and the net or local charge of protein, chemically modified cytochrome f, in which positively charged amino groups are replaced with negatively charged carboxyl groups, has been prepared by using an arylating reagent 4-chloro-3,5-dinitrobenzoic acid. Four distinct species of chemically modified cytochrome f, having 1 to 4 mol of modified amino residues per mol of cytochrome f, were separated by preparative polyacrylamide gel electrophoresis. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…1 for the locations of some of the charged residues). Chemical modification of acidic residues in plastocyanin [10,11], or of basic residues in cytochrome f [12,13], resulted in decreased rates of electron transfer from cytochrome f to plastocyanin. Electron transfer rates between cytochrome f and plastocyanin were also markedly decreased at increased ionic strength [14–16].…”
mentioning
confidence: 99%
“…1 for the locations of some of the charged residues). Chemical modification of acidic residues in plastocyanin [10,11], or of basic residues in cytochrome f [12,13], resulted in decreased rates of electron transfer from cytochrome f to plastocyanin. Electron transfer rates between cytochrome f and plastocyanin were also markedly decreased at increased ionic strength [14–16].…”
mentioning
confidence: 99%
“…Cytochrome f is anchored in the membrane by a hydrophobic membrane‐spanning region near the C terminus with the bulk of the protein protruding into the thylakoid lumen where it can interact with plastocyanin [1,3]. The interaction of soluble forms of cytochrome f with plastocyanin has been extensively studied in vitro , and the importance of electrostatic interactions has been clearly demonstrated by kinetic measurements at different ionic strengths [4,5] and with proteins modified chemically [6–9] or by site‐directed mutagenesis [10,11]. Chemical cross‐linking and modelling studies have highlighted the interaction of acidic residues on plastocyanin with basic residues on cytochrome f [12–14].…”
mentioning
confidence: 99%
“…The negatively charged region is generally accepted to be required for electrostatic interactions with cytochrome f and photosystem I, and His-87 on the hydrophobic region is thought to act as an electron-donating residue to P700 + [3,14]. Some site-directed mutagenesis studies and biochemical evidence indicated that Tyr-83 functions as an electron-accepting residue from cytochrome f [15][16][17][18][19]. Subsequently, Ubbink et al [20] reported the structure of physically tangible plastocyanin/ cytochrome f complex, and confirmed the electrostatic interaction between the negatively charged region of plastocyanin and the positively charged region of cytochrome f, and that the hydrophobic region of plastocyanin makes close contact with the heme residue of cytochrome f. Based on this structural information, they argued for a short electron transfer pathway via the copper ligand His-87, not Tyr-83 [20].…”
Section: Unique Phe-82-phe-83 Motifmentioning
confidence: 99%